Analysis of the Effectiveness of the Distribution of Zakat Funds through the Prosperous North Sumatra Program at the National Baznas of North Sumatra Province - Wahyu Sahara Ramadhana Manurung; Marliyah Marliyah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to determine the effectiveness of the distribution of zakat funds through the North Sumatran Makmur program at BAZNAS of North Sumatra Province and how the process of distributing zakat funds in carrying out the North Sumatran Makmur program. This type of research uses qualitative research with a descriptive approach and the data analysis used in this research is descriptive qualitative analysis. The tools used in data collection in this study were the results of observations, interviews, and documentation. The results of this study are from the institutional side, the distribution of zakat in terms of the implementation of empowerment carried out by BAZNAS North Sumatra Province has been implemented and is running well but from the other side there are several things that have not reached the level of effectiveness, because there is no accompanying team needed by BAZNAS to assist the process of distributing zakat funds and in terms of mustahik the distribution of zakat funds in implementing the North Sumatra Makmur program is also not effective because there is still a lack of available funds in the implementation of this program, so that mustahik cannot receive funds according to their business needs.